(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article is devoted to rethinking the history of the Kokand Khanate. The Kokand Khanate existed for 167 years (1709-1876) and in the middle of the 19th century it turned into a local power. It consisted of modern Uzbekistan, Kyrgyzstan, the Southeastern side of Kazakhstan and the north of Tajikistan. During the years of Soviet power, scientific research demanded: “strictly observe the Marxist-Leninist approach,” “avoid nationalist tendencies and do not idealize historical figures.” The article examines the history of the Khanate on the basis of new narrative and archival sources and provides a new scientific perspective.